PTU-186 12 Month outcome and Patient Satisfaction with Structured Gastroenterological Evaluation for Chronic Gastrointestinal Symptoms following Pelvic Radiotherapy. (4th June 2013) - Henson, C C; McLaughlin, J; Ang, Y; Babbs, C; Crampton, J; Kelly, M; Lal, S; Limdi, J K; Whatley, G; Swindell, R; Makin, W; Davidson, S E
Abstract : Introduction: Seventeen thousand patients are treated with radical pelvic radiotherapy annually in the UK.50% develop chronic GI symptoms. The structured approach to management used in this service evaluation has been shown to identify treatable diagnoses and improve symptoms in the short term. We report the first 12 month outcome data for the effect of structured gastroenterological evaluation on symptom burden and patient satisfaction. Methods: Fifty-six patients with GI symptoms > 6 months after radical pelvic radiotherapy underwent structured gastroenterological assessment as part of a service evaluation. They were assessed using the following questionnaires: inflammatory bowel disease questionnaire(IBDQ); Vaizey incontinence questionnaire (VIQ); and the Common Terminology Criteria for Adverse Events (CTCAE)pelvic symptom questionnaire.12 month assessments were compared to the previously reported baseline and 6 month assessments to determine if the improvement in symptoms was sustained. Patient satisfaction with the service was assessed at 12 months by an in-house questionnaire. Results: Forty patients(71%)completed the 12 month assessment and 37(66%) completed the patient satisfaction questionnaire. The initial statistically significant improvement in GI symptoms from baseline to 6 months in parallel to GI evaluation was sustained up to 12 months in all questionnaires (IBDQ p = 0.019, IBDQB and CTCAE rectum bowel subset p < 0.0005) except the VIQ (p = 0.098).There was also a clinically significant improvement as defined by an increase in IBDQ score of ≥0.5 points per question. Median total IBDQ and IBDQB score increased by 25 and 11 points respectively between baseline and 12 months.97% of patients found the appointments convenient, 97% felt their problems were understood; 86% were satisfied with the outcome and 89% with the service. Dissatisfaction related to communication (n = 3), travel (n = 2) and ongoing symptoms (n = 3). Conclusion: The clinically and statistically significant improvement in GI symptoms found in parallel to structured gastroenterological evaluation for chronic GI symptoms following pelvic radiotherapy was sustained over 12 months follow up. These data suggest that structured investigation on the basis of the BSG guidelines can lead to a sustained improvement in symptoms and is acceptable to patients. Further research is essential to optimise patient care. Disclosure of Interest: None Declared.